Measuring the Effective Factors in the Non-Development of the Sustainable Smart City of Tabriz - Ali Zeynali Azim; Mehri Fadaei Haghi; Amin Alizadeh; Mohammad Jodeiri Abbasi; Reza Fathipour; Mohammadali Sharifi (علوم محیطی)
Introduction: Tabriz city, like most big cities in the world, is facing complex problems in terms of population density, air and noise pollution, providing transportation services, social, economic housing and other issues. Therefore, the formation of a smart city based on smart criteria in the city of Tabriz based on big data can be a great help for government and city managers to determine the strategy of a smart city. The reason for the lack of success in the implementation of the smart city is the lack of awareness of the smart city and its management and the effective factors in its formation. Therefore, it is very necessary and vital to identify the effective factors in the formation of a sustainable smart city of Tabriz at this time. The purpose of this study is to identify the effective factors in the development of a sustainable smart city and its characteristics in the city of Tabriz based on a developed model. Achieving urban sustainability through smart cities is necessary to manage urban problems that threaten human survival. Smart city policies include various social, economic, physical and environmental aspects and provide the possibility of developing practical plans for urban sustainability. The purpose of this research is to measure the factors affecting the non-development of a sustainable smart city in Tabriz. Material and Methods: The research method is descriptive-exploratory. It is functional in purpose. The statistical population of the research includes experts and specialists in urban planning and professors. The sample size is 46 people. To analyze the data using the structural equation method, the final part describes the confirmatory factor analysis using the structural equation model (SEM). SPSS software was used for data analysis. SEM modeling was done using AMOS software. The confirmatory factor analysis (CFA) model was conducted using various factors of sustainable smart city development such as traffic problems, parking problems, stormwater problem, waste management, road safety problems, pollution problems, drinking water problems and crime-related problems. AMOS software was used to perform structural equation modeling (SEM). Results and Discussion: The results showed that the traffic problem with a factor load of 0.958 has the greatest impact and the flood problem with a factor load of 0.451 has the least impact among the factors affecting the development of the sustainable smart city of Tabriz. Also, the goodness-of-fit index (GFI) was 0.946, which indicated the acceptability of this amount for the optimal fit of the model. The value of the root mean square error of estimation (RMSEA) was 0.057, which is acceptable considering that it is smaller than 0.08, and it indicates the confirmation of the research model. Therefore, it can be concluded that the CFA model is valid, and the selected parameters can contribute to the development of a sustainable smart city in Tabriz. Conclusion: The biggest challenge in planning and constructing the smart city of Tabriz is identifying the real needs of the people, raising public awareness, especially among urban management, and explaining the mechanisms and benefits of smart initiatives. This includes understanding the people's share of these benefits and promoting public participation in areas such as traffic management, urban waste management, air pollution, and crime-related issues. Neglecting these aspects has negatively impacted the quality of life and general well-being of society, causing disruptions in service provision. This study offers in-depth knowledge on implementing various aspects of the smart city plan and suggests solutions for further developing the factors that contribute to the sustainability of the smart city of Tabriz.